Islamism in South Sulawesi: Studies on the Activism of PKS and Hizb Tahrir Indonesia - Syahrir Karim; Samsu Adabi Mamat (Universitas Islam Negeri Alauddin Makassar, 2013)
Partai Keadilan Sosial (PKS) and Hizb ut- Tahrir Indonesia (HTI) are two Islamic political movements in Indonesia with controversies and political sensations. In terms of organization, the two movements have a strong emotional connection historically and ideologically. Both are of transnational Islamic based movements, although in the end they perform their roles in different domains: PKS works at the level of intra- parliamentary with a formal political party label while HTI works in the region of extra-parliamentary and is labeled as a non-formal organizational movement. HTI, which rejects democratic system, turns out to enjoy Indonesian democracy as